From Bystanders to Upstanders: Evaluating the Impact of CEMBUNGS Empowerment Program on Bullying Prevention in Indonesian Senior High Schools (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Cases of bullying in high schools are increasingly concerning. Many prevention programs have been carried out but are still not optimal. This is due to the low level of awareness of students to act proactively in stopping bullying. The CEMBUNGS Empowerment Program was designed with the aim of increasing students' understanding and awareness of bullying prevention and equipping them with social skills and empathy to create a safe and comfortable school environment. This service activity was carried out by taking a mixed-methods approach, combining a quantitative approach (health education) through pre-test and post-test on 37 students and a Qualitative approach on 10 students through an FGD conducted at one of the State High Schools in Pangandaran Regency.  Based on the results of the pre-test and post-test analysis, it showed an increase in understanding of 0.62 point. These results indicated that an educational approach with the lecture method was effective in increasing students' knowledge related to bullying. Meanwhile, the FGD activities carried out can provide a space to explore students' understanding and discuss ideas to create a safe environment. The program was quite effective in increasing students' knowledge, fostering awareness of the importance of bullying prevention, and providing space for students to be involved in creating a conducive school environment. Recommendations for follow-up programs can be conducted to assess long-term evaluations and measure the impact of previously implemented programs on student behavior in the school environment.